2018
DOI: 10.1525/mp.2018.35.3.364
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Aural and Visual Information in the Evaluation of Western Canon Music Performance by Musicians and Nonmusicians

Abstract: AURAL AND VISUAL INFORMATION HAVE BEENshown to affect audience evaluations of music performance (Griffiths, 2010;Juslin, 2000); however, it is not fully understood which modality has the greatest relative impact upon judgements of performance or if the evaluator's musical expertise mediates this effect. An opportunity sample of thirty-four musicians (8 male, 26 female M age ¼ 26.4 years) and 26 nonmusicians (6 male, 20 female, M age ¼ 44.0 years) rated four video clips for technical proficiency, musicality, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…As such, participants would have relied on one input over the other, which in turn would reduce their desire to move, compared to the possible additive effect that was likely present for the two modalities in the fully-corresponding condition. Indeed, Griffiths and Reay (2018) recently showed that incongruent audio-visual pairings can lead to the visual component having the greatest influence on an audience member's evaluation of a musical performance. A similar result was not observed for the second incompatible condition which displayed asynchronous body movement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, participants would have relied on one input over the other, which in turn would reduce their desire to move, compared to the possible additive effect that was likely present for the two modalities in the fully-corresponding condition. Indeed, Griffiths and Reay (2018) recently showed that incongruent audio-visual pairings can lead to the visual component having the greatest influence on an audience member's evaluation of a musical performance. A similar result was not observed for the second incompatible condition which displayed asynchronous body movement.…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of studies investigating music evaluation of liking, expressiveness and performance quality, Platz and Kopiez (2012) found a medium effect size for the visual component. There is also some evidence that visual information has a relatively greater effect on audience ratings of performance quality compared to audio information (Griffiths & Reay, 2018).…”
mentioning
confidence: 99%
“…Such gestures can provide additional information about the music's expressive and structural properties, thus enabling the audience to enter into a more engaging internal dialog with the musical pieces. For example, it has been shown that musical expertise can be perceived through performer movement, even in the absence of any auditory information pointing to a substantial effect of performers' movements and gestures (Tsay, 2013;Griffiths and Reay, 2018). Additionally, performative and expressive movements of instrumentalists (Davidson, 1993(Davidson, , 2012Broughton and Stevens, 2009;Vines et al, 2011;Silveira, 2014;Vuoskoski et al, 2014), singers (Davidson, 2001;Lange et al in review), and conductors (Luck et al, 2010;Morrison and Selvey, 2014), show that gestures can increase perceived expressivity of the music.…”
Section: Effects Of Multi-modal Perceptionmentioning
confidence: 99%
“…Volpe, D'Ausilio, Badino, Camurri, & Fadiga, 2016) may provide a better understanding of the broad repertoire of body movements utilized to cooperate and coordinate with co-performers and to communicate expressiveness to audience members during musical performances. These bodily gestures need also to be taken into account when determining an observer's appreciation or liking of a musical performance (Griffiths & Reay, 2018;Thompson, Graham, & Russo, 2005). Understanding the process of judging ensemble performances (Tsay, 2014), or specific musicians within an ensemble, will require a careful investigation of visual and auditory cues as well as consideration of observers' visual and auditory expectations in performance settings.…”
Section: Discussionmentioning
confidence: 99%